The Relationship between Strategic Planning, Managerial Competence, and Competitive Advantage on Organizational Performance - Ermansyah; Mulia Sosiady (Malaqbi Publisher, 2026)
This study examines the relationship between strategic planning, managerial competence, competitive advantage, and organizational performance within an integrated structural framework. Drawing on the resource-based view and dynamic capabilities theory, the research investigates both the direct effects of strategic planning and managerial competence on organizational performance and the mediating role of competitive advantage. A quantitative approach was employed using survey data collected from 245 managers across various industries. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that strategic planning and managerial competence significantly and positively influence organizational performance. Competitive advantage was found to be the strongest predictor of performance and also partially mediates the relationships between strategic planning and performance, as well as between managerial competence and performance. These results indicate that while effective planning and competent managerial leadership directly enhance organizational outcomes, their impact is strengthened when they contribute to the development of sustainable competitive advantage. The study provides theoretical contributions by integrating strategic management and capability perspectives into a comprehensive performance model. Practically, the findings suggest that organizations should align strategic planning processes, managerial capability development, and competitive positioning strategies to achieve sustained performance in dynamic and competitive environments.